Taxonomic revision of Sabicea subgenus Anisophyllae (Ixoroideae, Rubiaceae) from Tropical Africa, with four new species - Zemagho, Lise A.; Liede-Schumann, Sigrid; Lachenaud, Olivier; Dessein, Steven; Sonke, Bonaventure (Phytotaxa, 2017)
A taxonomic revision of Sabicea subgenus Anisophyllae (Rubiaceae), a group restricted to Central and East Africa, is presented here. This work, based on a study of herbarium specimens and field observations in Cameroon and Gabon, includes a survey of the morphological features of the group, a key to the species, descriptions of all the taxa, and IUCN conservation status assessments. Fifteen species are recognised, four of which are described as new (Sabicea mapiana, S. ndjoleensis, S. parmentierae, S. sciaphilantha), three former varieties are raised to species rank (S. crystallina, S. jacfelicis, S. tersifolia), and one species previously sunk into synonymy is restored (S. bequaertii). Two new infraspecific taxa are also described, Sabicea crystallina subsp. engongensis and S. sciaphilantha subsp. hirsuta. The group has its center of diversity in Gabon, where 10 of the 15 species occur, three of them being endemic to the country.